Root anomalies – tearing and supernumerary root: Integrative literature review (Research, Society and Development, 2022)
Objective: to carry out an integrative literature review that presents results in scientific scientific databases about root anomalies - laceration and supernumerary root; perform the synthesis of information about root anomalies - laceration and complete supernumerary root in the literature; to list the importance of such knowledge for the improvement of dental care. Methodology: This is an exploratory and descriptive study with a qualitative approach of the Integrative Literature Review (RIL) type. Using Iramuteq to list the discursive classes of the analysis of selected articles. the chosen database was the VHL (virtual health library), these were used the following inclusion criteria: texts available for free and in the database; texts in Portuguese and English; texts published between 2010 - 2020; text that contemplated the addressed theme. Results and discussion: 5 articles were selected from the database search among these articles 3 were from 2012, one from 2015 and one from 2020, exposing the lack of articles on the subject, in relation to the discursive classes listed by iramuteq, the result was) Treatments for root anomalies and patient suffering; 2) Effects of tooth position and angulation on root tear; 3) Radiography as a fundamental exam for the treatment of root anomalies; 4) factors that contribute to root anomalies.